2019
DOI: 10.1016/j.ijbiomac.2019.03.161
|View full text |Cite
|
Sign up to set email alerts
|

Construction, expression and antiviral activity analysis of recombinant adenovirus expressing human IFITM3 in vitro

Abstract: Interferon-inducible transmembrane protein 3 (IFITM3) inhibits the replication of multiple pathogenic viruses by blocking their entry. In this study, we constructed a shuttle plasmid, harboring human IFITM3. Thereafter, recombinant adenovirus rAd5-IFITM3 was obtained by co-transfection of the linearized viral backbone vector pAd5 and the shuttle plasmid. The results showed that human IFITM3 did not affect the assembly and morphogenesis of progeny adenovirus. Human IFITM3 can be expressed in both A549 and MDCK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Further research shows that silencing IFITM3 of U2OS cells can strongly enhance the replication of IAV H1N1 (A/PR/8/34), and siRNA targeting IFITM3 has a significant effect on eliminating IFN-g mediated virus inhibition (2). We previously found that IFITM3 can suppress H5N1 replication in the early stage of the infection (10). Moreover, overexpression of human IFITM1, 2, or 3 inhibits replication of an IAV H1N1 subtype (A/PR/8/34) and H3N2 subtype (A/Udorn/72) (2,24,25).…”
Section: The Antiviral Spectrum Of Ifitmsmentioning
confidence: 98%
See 1 more Smart Citation
“…Further research shows that silencing IFITM3 of U2OS cells can strongly enhance the replication of IAV H1N1 (A/PR/8/34), and siRNA targeting IFITM3 has a significant effect on eliminating IFN-g mediated virus inhibition (2). We previously found that IFITM3 can suppress H5N1 replication in the early stage of the infection (10). Moreover, overexpression of human IFITM1, 2, or 3 inhibits replication of an IAV H1N1 subtype (A/PR/8/34) and H3N2 subtype (A/Udorn/72) (2,24,25).…”
Section: The Antiviral Spectrum Of Ifitmsmentioning
confidence: 98%
“…It is reported that IFITM proteins could significantly inhibit IAV, West Nile virus (WNV), Ebola virus (EBOV), SARS coronavirus (SARS-CoV), vesicular pharyngitis virus (VSV), Rift Valley fever virus (RVFV), dengue virus (DENV), Semliki forest virus (SFV), Zika virus, Respiratory syncytial virus (RSV), human immunodeficiency virus-1 (HIV-1), hepatitis C virus (HCV), Reovirus, and other capsular or noncapsular RNA viruses (2)(3)(4)(5)(6)(7)(8)(9)(10). Besides this, IFITM proteins also exhibit antiviral activity against individual DNA viruses (5,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…TLR and RLH differ in their cellular localization, ligand specificity, and downstream signaling pathways, suggesting that host cells have multiple defense mechanisms against viral infection. Among ISGs, 2′–5′-oligoadenylate synthetase (OAS) plays a critical role in antiviral immunity by synthesizing 2–5As, which induces RNA degradation by activating a latent RNase (RNase L) pathway [ 34 ].…”
Section: Inflammatory Response and Ifitm3 Role In Influenza A Virumentioning
confidence: 99%
“…For all viruses, the earlier the cells were transduced by Ad-caIFNλ3, the greater the suppression of both viral genome and protein levels. This could be the result of earlier expression of canine IFNλ3 by the recombinant adenovirus (Du et al 2019 ). In a similar context, inhibitory effects were better in a dose-dependent manner, showing better prevention in the cells treated with an MOI of 100 than those treated with an MOI of 10.…”
Section: Discussionmentioning
confidence: 99%